Hydraulic conductivity of yellow-red latosol - Stone, Luis Fernando; Silveira, Pedro Marques da (Pesquisa Agropecuaria Brasileira, 2014)
The present study was conducted at the National Rice and Bean Research Center, Goiânia, GO, with the objective to determine hydraulic conductivity of a distrophic Yellow-Red Latosol by Hillel's method. The relationships between hydraulic conductivity and soil-water content were K = 10-10,19195 + 36,11647 θ and K = 10-8,01559 + 31,24924 θ for the 0 – 30 cm and 30-60 cm depths, respectively.